Search 72,249 tutors
FIND TUTORS
Ask a question
0 0

6(5-a)-(1-a)=2. Find a.

Tutors, please sign in to answer this question.

1 Answer

6(5-a) - (1-a) = 2
 
First distribute (multiply) the 6 across the terms in the parentheses:
 
6*5 - 6*a - (1-a) = 2
30 - 6a - (1-a) = 2
 
When you subtract terms within parentheses, such as -(1-a), change the sign of each term and add them; that is -(1-a) = + (-1) + a = -1 + a:
 
30 - 6a + (-1) + a = 2
30 - 6a - 1 + a = 2
 
Combine like terms:
 
(30-1) + (-6a+a) = 2
29 - 5a = 2
 
Now solve for a:
 
29 - 2 = 5a
27 = 5a
27/5 = a